1978
DOI: 10.1590/s0373-55241978000200005
|View full text |Cite
|
Sign up to set email alerts
|

An annotated bibliography of parasitic Isopoda (Crustacea) of Chondrichthyes

Abstract: SYNOPSISThis annotated bibliography is an attempt to bring together alI available published records on the parasitic isopods of Chondrichthian fishes as a basic reference source. An effort was made to synonymise old names according to the presently accepted scientific names. I NTRODUCTI ONData on the occurrence of parasitic isopods on Teleostean are quite abundant. However, references to their occurrence on Chondrichthian fishes are scattered and less numerous.The purpose of the present work ~s to assemble pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…According to Moreira & Sadowsky (1978), Trilles (1994) and the present study, 20 cymothoids have now been reported on chondrichthyan hosts:…”
Section: Review Of All Cases (Excluding Cephalopods) Of Unusual Cymotsupporting
confidence: 55%
“…According to Moreira & Sadowsky (1978), Trilles (1994) and the present study, 20 cymothoids have now been reported on chondrichthyan hosts:…”
Section: Review Of All Cases (Excluding Cephalopods) Of Unusual Cymotsupporting
confidence: 55%
“…Numerous species of isopods in the family Cirolanidae, and in related families, are known scavengers and occasional micropredators on fishes (for summaries see Moreira & Sadowsky 1978, Kussakin 1979, Brusca & Iverson 1985. Similarly, ostracod species of the family Cypridinidae have been reported as occasional scavengers or 'biters' or actual parasites on other marine animals (Monod 1923, Harding 1966, Felder 1982, Cohen 1983, Kretzler 1984.…”
Section: Study Site]mentioning
confidence: 99%
“…Cheung & Nigrelli (1983) rediscovered this parasite (as N. ruggierii; see synonymy of Chisholm 1994) and described the skin-infecting monogenoid Dermophthirioides pristidis Cheung & Nigrelli 1983 (Microbothriidae) from smalltooth sawfish collected in the Florida Keys. There are a few, brief mentions of the isopods Livoneca ovalis (Say, 1818) (sometimes as Lironeca ovalis) and Nerocila acuminata Schiödte & Meinert, 1881 (Cymothoidae) infecting unspecified sawfish (Moreira & Sadowsky 1978); however, empirical data are wanting, and a single listing from a venerable monograph on isopods (Richardson 1905) seems the likely source of later listings until the present study. Hutton (1964) anecdotally reported metacercariae of the trematode Scaphanocephalus expansus (Creplin, 1842) as a parasite of the smalltooth sawfish from the eastern Gulf of Mexico near Tarpon Springs, Florida.…”
Section: Introductionmentioning
confidence: 82%